SISTEM TASKLIST DENGAN MENGGUNAKAN METODE GAMIFIKASI UNTUK PERANKINGAN KARYAWAN PADA DEPARTEMENT OPERASIONAL SOLUTION PT. VISIONET DATA INTERNATIONAL - Rizki Riswandi; Andi Rahman H; Laura Adelia M; Novianti Rizky; Rifqi Rahmansyah (CV. Denasya Smart Publisher, 2025)
This research aims to develop a gamification-based tasklist system designed to increase efficiency in the division of tasks while motivating employees in the Operational Solution Department of PT. International Data Visionet. During its development, this system integrated various gamification elements, such as a ranking feature that encourages healthy competition between employees, digital awards that provide appreciation for certain achievements, and a performance points system that aims to increase accountability and work productivity. The system development process is carried out using the Waterfall methodology approach, which involves the stages of requirements analysis, system design, implementation, testing, and maintenance. System testing is carried out using the Blackbox Testing method to ensure that all system functions run according to predetermined specifications. This system is designed with a user-friendly interface, making it easier for employees to understand and use its features.